Evaluation of the Legal Regulation on Prevention Against Violence in Health, Dated April 2020 - Taştemir, S. Yazgülü; Akay, Arda; Balcı, Işılay; Yorulmaz, A. Coşkun (The Bulletin of Legal Medicine, 2022)
Violence has been accepted as an important public health problem by the World Health Organization (WHO) as of 2002. As in every discipline, the concept of violence has been defined in different ways in studies dealing with violence against healthcare workers. According to the World Health Organization; violence is defined as "the intentional use of physical force or power, threatened or actual, against oneself, another person, or against a group or community, that either results in or has a high likelihood of resulting in injury, death, psychological harm, maldevelopment, or deprivation. “As in the rest of the world, there are incidents of violence against healthcare workers in our country and researches and arrangements are made on this subject both in academic level and in terms of social policies. In this study, the regulation that came into force on 17.04.2020 for the prevention of violence against healthcare workers in our country will be examined.
Keywords: Violence, Healthcare Worker, Legal Regulation.